New taxa and distributional notes on Abbottella and related taxa (Gastropoda: Littorinoidea: Annulariidae) - Watters, G. Thomas (Zootaxa, 2013)
Seven new species of Abbottella and related taxa are described from Hispaniola: Abbottella calliotropis n. sp., Abbottella diadema n. sp., Abbottella dichroa n. sp., Abbottella nitens n. sp., Abbottella paradoxa n. sp., Abbottella tenebrosa n. sp., and Leiabbottella thompsoni n. sp. Distributional and habitat notes are given for additional taxa.